PROBLEMATIKA ALUMNI PAI SEBAGAI GURU KELAS DI MADRASAH IBTIDAIYAH SEKECAMATAN PANGKALAN SUSU KABUPATEN LANGKAT - Roys Afreni (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study was conducted with regard to the phenomenon of Islamic religious education graduates who became class teachers in Madrasah Ibtidaiyah Pangkalan Susu distric. The purpose of this research is to know: 1) Problematic graduates of PAI as classroom teachers in planning instructional. 2) Problematic graduates of PAI as classroom teachers in implementing instructional. 3) Problematic graduates of PAI as classroom teachers in conducting instructional evaluation. The type of research is using qualitative research methods with phenomenology approach. The subject of research is the graduate of Islamic Religious Education who has become a class teacher. The result of the research that problematic of PAI graduates as teacher of Madrasah Ibtidaiyah class in planning instructional in Pangkalan Susu sub-district of Langkat district is still having difficulties to make instructional plan independently. Besides these three Madrasah Ibtidaiyah also do not have a library that can provide books that qualified to be used as a source of learning. While in implementing the instructional is the similarity of teachers in the method of learning and the lack of mastery of the material. This is due to their lack of knowledge about the variety of instructional methods and the lack of mastery of the material. On the other hand these teachers rarely attend training, seminars, workshops that can provide information for development for their profession. As for the evaluation of learning is not yet meet the assessment procedures. This is because the teacher has not understood the way the preparation of the implementation Plan of instructional.